Ergonomics modeling of human height from stride length for adult population in South Western, Nigeria - Musa, Adekunle Ibrahim; Musa, Ayomide Idris; Ogedengbe, Temitayo Samson (Engineering and Applied Science Research, 2023)
The crime gauging in Nigeria have increased unexpectedly. The Identification of criminals has also constituted a great danger to the justice of the criminal acts. This study was conducted to appraise the relationship between Human heights (HH), Stride length (SL) and subsequently deduce models for the justice of criminals. A total of nine hundred and fifty six (956) participants, (486 males and 470 females) were assessed. The ages of the participants were between 25 years and 60 years. The human height and stride length of the participants were measured and recorded. The data obtained were analysed using SPSS 23.0 version software to establish the model equations for the HH. The result shows that male individuals possess higher mean value of HH and SL than female counterparts. The model equations obtained were validated with the direct measurement of HH. The present study has clearly demonstrated that SL can be used in the judgment of HH. The authors recommended further and elaborate research in other geo-political region of Nigeria, so as to build a database for Nigerian population.